섬유제품 상변화물질 관련 특허통계 분석을 통한 한국과 미국의 기술개발동향 -특허정보검색 중심으로 - 유화숙; Hwa Sook Yoo; 박광희; Kwang Hee Park; 김문영; Moon Young Kim (한국의류산업학회지, 2007)
Phase change material-related patents filed at Korea Institute of Patent Information(KIPI) and United States Patent and Trademark Office(USPTO) were analyzed for understanding the PCM's technological level of Korea and providing the information for establishing the research development policy concerned with high technology fibers. Patent data from 1980 to 2005 collected from KIPI and USPTO internet sites were examined using the number of patents and share of assignees in patents. The contents of patent were classified according to IPC(International Patent Classification) and assignees were divided into individual and firm/public body. The results of comparing total number of patents in USA with that in Korea showed USA had as 2.3 times as Korea had. The number of patents of USA had increased steadily since 1980 whereas that of Korea sharply since 2001. The number of patents of Korea from 2001 to 2005 was more than that of USA. USA was specialized in fundamental technology and Korea was specialized in application area with PCM. Assignees who had the most patents were firms and the next were individuals. Assignees who applied for several patents were more in USA than in Korea and patent application numbers per the assignees were higher for USA.